Heat damage evaluation in carbon fiber-reinforced composites with a kHz A-scan rate fiber-optic pump-probe laser-ultrasound system. (May 2016) - Pelivanov, Ivan; Ambrozinski, Łukasz; O'Donnell, Matthew
Abstract: Composites are increasingly replacing metals for a number of applications where their reduced weight and equivalent strength compared to metals is extremely important. As composite structures become more routine, non-destructive tools are needed to monitor their structural integrity when subjected to different damage mechanisms, such as impact and thermal insults. Here we present a non-contact laser-ultrasound (LU) method to quantify and image structural changes in carbon fiber reinforced polymer (CFRP) composites induced by thermal insult. The method uses ultra-wideband acoustic signals generated at the surface of a composite material with a laser pulse (i.e., pump), and non-contact, point-like detection of backscattered transients (i.e., probe). A comparison of results from the LU system with X-ray images of thermally insulted samples shows that high-resolution LU images (better than 1 ply) and spectral analysis of backscattered signals can identify small structural changes in composites long before delamination.